1996
DOI: 10.1016/0014-2999(96)00302-0
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural effects of 7-OH-DPAT are solely due to stimulation of dopamine D2 receptors in the shell of the nucleus accumbens; turning behaviour

Abstract: The goal of this study was to determine whether the dopamine D3 receptor in limbic structures plays a role in the shell-specific and dopamine-dependent display of turning behaviour in rats. When combined with the dopamine receptor agonist (± )-i-phenyl-2,3,4,5-tetrahydro-1 //-3-benzazepine-7,8-diol (SKF-38393, 5 jx g ) , the putative dopamine D3 receptor agonist (±)-7-hydroxy-/V,N-di-n-propyl-2-aminotetralin (7-OH-DPAT, 1, 5 and 10 jJLg) elicited contralateral turning in a dose-dependent manner following unila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Accordingly, S32504 dose-dependently, stereospecifically, and potently elicited contralateral rotation, an action mimicked (less potently) by ropinirole and L-DOPA (Eden et al, 1991). Although structures other than the striatum are implicated in the motor drive underlying rotation, it principally reflects a supersensitivity (enhanced density) of striatal D 2 receptors (Koshikawa et al, 1996;Araki et al, 2000;Newman-Tancredi et al, 2001). Correspondingly, extending studies with a further D 2 /D 3 agonist, quinerolane (Newman-Tancredi et al, 2001), S32504-induced rotation was blocked by the preferential D 2 receptor antagonist L741,626 but not by the selective D 3 receptor antagonist S33084 (Millan et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Accordingly, S32504 dose-dependently, stereospecifically, and potently elicited contralateral rotation, an action mimicked (less potently) by ropinirole and L-DOPA (Eden et al, 1991). Although structures other than the striatum are implicated in the motor drive underlying rotation, it principally reflects a supersensitivity (enhanced density) of striatal D 2 receptors (Koshikawa et al, 1996;Araki et al, 2000;Newman-Tancredi et al, 2001). Correspondingly, extending studies with a further D 2 /D 3 agonist, quinerolane (Newman-Tancredi et al, 2001), S32504-induced rotation was blocked by the preferential D 2 receptor antagonist L741,626 but not by the selective D 3 receptor antagonist S33084 (Millan et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Injected individually, these agonists were ineffective at producing turning, and the effect was attenuated by injection of SCH‐23390 (D 1 antagonist) or l‐sulpiride (D 2 antagonist). Additional study 78,79 revealed that injections of D1 (SKF 82958) and D3 (7‐OH‐DPAT) receptor agonists also produced contralateral turns and jaw movements when injected together into shell (see also refs. 80 and 81).…”
Section: Some Recent Functional Studiesmentioning
confidence: 97%